2020
DOI: 10.3390/ijerph17165843
|View full text |Cite
|
Sign up to set email alerts
|

Dental Health Services Response to COVID-19 in Norway

Abstract: We aimed to investigate the management of urgent dental care, the perception of risk and workplace preparedness among dental staff in Norway during the COVID-19 pandemic. An electronic questionnaire regarding the strictest confinement period in Norway (13 March–17 April 2020) was distributed to dental staff. Among the 1237 respondents, 727 (59%) treated patients, of whom 170 (14%) worked in clinics designated to treat patients suspected or confirmed to have COVID-19. Out of them 88% (143) received training and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 32 publications
3
24
0
Order By: Relevance
“…Additionally, an increased workload associated with inadequate personal protection equipment (PPE), causing concerns of nosocomial transmission that may result in physical exhaustion, anxiety, and even stress [ 16 , 17 , 18 , 19 , 20 ]. Similar studies that only focused on dental assistants or students confirmed these results [ 21 , 22 ]. However, all groups dealing with patients, dentists, dental assistants, students, and patients have to follow a pandemic concept focusing on the well-being of all persons involved [ 23 ].…”
Section: Introductionsupporting
confidence: 71%
“…Additionally, an increased workload associated with inadequate personal protection equipment (PPE), causing concerns of nosocomial transmission that may result in physical exhaustion, anxiety, and even stress [ 16 , 17 , 18 , 19 , 20 ]. Similar studies that only focused on dental assistants or students confirmed these results [ 21 , 22 ]. However, all groups dealing with patients, dentists, dental assistants, students, and patients have to follow a pandemic concept focusing on the well-being of all persons involved [ 23 ].…”
Section: Introductionsupporting
confidence: 71%
“…The reasons for this and the economic impact should be further investigated. The significant patient decline is also reported in a Norwegian study; twice as many patients were treated by telephone compared to clinical care [18]. This fact is also reported from China [20], where numerous public dental hospitals stopped the elective treatment of patients and only offered emergency treatment.…”
Section: Economic Effects On Dental Practicesupporting
confidence: 54%
“…However, in Switzerland, there is no additional local/national recommendation for the use of visors or headsets in the dental practice. While dentists in the present report provided similar information on protective materials in all COVID-19 prevalence areas, in Norway, a small proportion of dental staff in high prevalence areas have been equipped with additional infection prevention measures compared to those in low and medium prevalence areas [18].…”
Section: Protective Measuresmentioning
confidence: 75%
“…The level of awareness regarding the potential decontaminating role of mouthwashes (by disrupting the membrane of the virus) is alarming as only 31.5% participants endorsed with the statement while 52.3% respondents acknowledged the viricidal activity of mouthwashes. A global survey by Tariq et al reported that 27.1% dental practitioners accord with the fact that mouthwashes could reduce the risk of COVID-19 infection, 35 however, majority of healthcare workers reported for using mouthwashes prior to dental services in a study by Mouhat et al 36 The key challenge to control COVID-19 infection is to reduce the number of virus particles in the oral cavity since infected respiratory particles play a primary role in the transmission of SARS-CoV-2 infection, effective strategies to disrupt the lipid envelop of these viruses need to be established. Oral rinses exhibit a prophylactic role in decontamination of mouth and subsequently destroying the membrane.…”
Section: Discussionmentioning
confidence: 99%